Costs and liabilities of US public pension systems in a low-return environment. (10th April 2021) - Chen, Gang; Matkin, David; Kang, Hyewon
Abstract: In recent years, a growing number of capital market professionals have projected a low-return environment in US investment portfolios – where returns in most asset classes are expected to drop below historical rates. While these specific forecasts may not fully materialize, it is natural for cyclical investment markets to go through extended periods of lower returns, creating significant risks for public pension systems which rely on investment returns to sustain their long-term solvency and offset budgetary contributions. This paper uses a simulation method to examine the long-term effect of a low-return environment on the unfunded liabilities and contribution costs of US public pension systems while considering the moderating effects of asset allocation strategies, amortization approaches, and contribution policies.